(Re)Visiting the North: Reflections from the Mushuau-nipi (George River) - Pollock, Rebecca (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2008)
Cultural narratives of northern wilderness are central to any understanding of the ongoing development of Canada, particularly as they relate to Aboriginal people and environmental change. This paper provides a critical interdisciplinary perspective on the related concepts of region, wilderness and landscape as they are used to describe the North. The literature review exposes the personal, political and ideological uses of landscape to better understand how places, like the George River of Nitassinan, Innu territory, are inscribed with contested meanings. Political discourses about places draw upon economic, cultural and scientific constructions of land and its use, while wilderness mythology continues to dominate public policies relating to park creation and protected area management. The Séminaires nordiques autochtones (Northern Aboriginal Seminars) held on the George River are presented as one prospect for mediating complex land use conflicts through dialogues about culture, wilderness, environment and development.